"How I Chose Research on Proteases or, More Correctly, How it Chose Me". Issue 1 (3rd December 2012) - Huber, Robert
<x xml:space="preserve">Abstract</x> Crystal clear: "I was lucky to choose protein crystallography as the focus of my research activity at a time soon after its foundation by Perutz and Kendrew". Nobel Laureate Robert Huber reflects on how protein crystallography has developed and now has a fundamental role in our understanding of biological processes.